2017
DOI: 10.4067/s0719-81322017000200119
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rate in dairy cows treated with human chorionic gonadotropin five days after insemination

Abstract: ABSTRACT. This study tested whether the administration of hCG five days after insemination increased progesterone concentration and pregnancy rate (PR) in dairy cows. A total of 989 lactating Holstein cows with different parity and number of prior services were used. Cows were inseminated after overt estrus or at a fixed-time. Five days post-insemination, cows were randomly assigned to two treatment groups: hCG (n=482), which received 3500 IU of hCG by intramuscular injection; and the control group (n=507), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Müller-Sepúlveda et al [45] in Chile reported a higher CR 1 (75.6%) in dairy and beef cows. Urzúa et al [46] in Mexico also reported CR 1 on human chorionic gonadotropin (hCG) five-day post-insemination treated group (47.5%) and control group (37.4%) of Holstein cows, and overall CR 1 (48.4%) was reported. There were many actions done to improve the CR 1 of dairy cows in different countries of the globe, for example, Hamid and Kamruzzaman [47] in Bangladesh reported on gonadotropin releasing hormone (GnRH) of one hour before, during or after AI treated group (71.1%) and control group (55.6%) of Holstein Friesian and local crossbred cows.…”
Section: Conception Rate At First Insemination (Cr 1 )mentioning
confidence: 95%
“…Müller-Sepúlveda et al [45] in Chile reported a higher CR 1 (75.6%) in dairy and beef cows. Urzúa et al [46] in Mexico also reported CR 1 on human chorionic gonadotropin (hCG) five-day post-insemination treated group (47.5%) and control group (37.4%) of Holstein cows, and overall CR 1 (48.4%) was reported. There were many actions done to improve the CR 1 of dairy cows in different countries of the globe, for example, Hamid and Kamruzzaman [47] in Bangladesh reported on gonadotropin releasing hormone (GnRH) of one hour before, during or after AI treated group (71.1%) and control group (55.6%) of Holstein Friesian and local crossbred cows.…”
Section: Conception Rate At First Insemination (Cr 1 )mentioning
confidence: 95%
“…On days 32 and 60 after fixed-time AI, all heifers were subjected to pregnancy diagnosis by transrectal ultrasonography. We followed the calculations of PR and embryonic loss based on previous reports ( Urzúa Gonzáleza et al., 2017 ) as follows. The PRs were defined as the proportion of heifers that were diagnosed as pregnant on days 32 or 60 after fixed-time AI, divided by the total number of bred heifers at fixed-time AI.…”
Section: Methodsmentioning
confidence: 99%
“…(2008) , and Sahu et al. (2014) , treatment of first GnRH irrespective of oestrous cycle stage resulted in an ovulation rate of only 31–49% and depends on the maturation stage of the follicles ( Colazo & Mapletoft, 2014 ) and ovarian structure ( Urzúa Gonzáleza et al., 2017 ) at the time of programme initiation. Because of the importance of ovarian structure, dairy cows with a functional CL at the time of first GnRH tretment had more pregnancy outcome than cows lacking a functional CL at first GnRH injection regardless of their ovulatory response to the first GnRH treatment ( Carvalho et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%